Duplicating Character in an existing medium into character animation - Lucas, Terry; Aminah, Abd Karim; Nur Afifah Vanitha, Abdullah (2011)
Character is a vital element in animation. Original animation is developed from idea and this initial process is followed by sketching and character animation.